La répétition comme stratégie d’apprentissage de la langue française - Mihoubi Zineb et Amrour Maria (كلية الاداب و اللغات, 2025)
Abstract This research aims to analyze repetition as a French language learning strategy, particularly among learners in the third year of middle school (3e AM). Our approach is firstly framed within a didactic perspective, exploring previous work on the teaching/learning of French as a foreign language and the role of repetition in the development of language skills. Secondly, we present the results of a survey conducted using three complementary tools: a survey addressed to middle school FLE teachers, parents, and learners in the third year of middle school; a questionnaire addressed to teachers; and semi-structured interviews conducted with third year of middle school students. This data highlighted both teachers' perceptions of the effectiveness of repetition and students' actual or perceived learning practices. Finally, this study compares teaching approaches to learners' strategic uses of repetition as a socio-affective strategy for assessments or as a cognitive strategy that supports long-term learning. It concludes that structured supervision of repetition is beneficial for promoting memorization, linguistic automatization, and student confidence in their oral and written production.
Cas des apprenants de 3ème AM Collège Boudrissa Mohamed- Khmais
Keywords: Mots clés : Répétition; stratégie cognitive; stratégies métacognitives; stratégies socioaffectives; mémorisation; automatisation.